A protein–protein interaction map reveals that the Coxiella burnetii effector CirB inhibits host proteasome activity - Mengjiao Fu; Yuchen Liu; Guannan Wang; Peng Wang; Jianing Zhang; Chen Chen; Mingliang Zhao; Shan Zhang; Jun Jiao; Xuan Ouyang; Yonghui Yu; Bohai Wen; et al. (PLoS Pathogens, 2022)
Coxiella burnetii is the etiological agent of the zoonotic disease Q fever, which is featured by its ability to replicate in acid vacuoles resembling the lysosomal network. One key virulence determinant of C. burnetii is the Dot/Icm system that transfers more than 150 effector proteins into host cells. These effectors function to construct the lysosome-like compartment permissive for bacterial replication, but the functions of most of these effectors remain elusive. In this study, we used an affinity tag purification mass spectrometry (AP-MS) approach to generate a C. burnetii-human protein-protein interaction (PPI) map involving 53 C. burnetii effectors and 3480 host proteins. This PPI map revealed that the C. burnetii effector CBU0425 (designated CirB) interacts with most subunits of the 20S core proteasome. We found that ectopically expressed CirB inhibits hydrolytic activity of the proteasome. In addition, overexpression of CirB in C. burnetii caused dramatic inhibition of proteasome activity in host cells, while knocking down CirB expression alleviated such inhibitory effects. Moreover, we showed that a region of CirB that spans residues 91–120 binds to the proteasome subunit PSMB5 (beta 5). Finally, PSMB5 knockdown promotes C. burnetii virulence, highlighting the importance of proteasome activity modulation during the course of C. burnetii infection. Author summary As the causative agent of Q fever, C. burnetii colonizes host cells by transferring effector proteins into the host cytoplasm through its Dot/Icm secretion system to construct a replicative vacuole. The function of effectors remains largely unknown. Here, we performed a large-scale AP-MS screen to analyze the interactions among C. burnetii effectors and human proteins. These analyses found that CirB functions as an inhibitor of host proteasome activity, revealing that proteasome activity is important for intracellular survival of C. burnetii. Our data have laid the foundation for future exploring the molecular mechanisms underlying the roles of C. burnetii effectors in its virulence and for the identification of novel potential drug targets for the development of novel therapeutic treatment for C. burnetii infection.